Who Wants to Live Forever?: Transhumanist Immortality and Christian Eternity - Eberl, Jason T. (Christian bioethics, 2025)
Transhumanists aim at immortality, or at least radical longevity, using various forms of cyber/biotechnology. The metaphysical possibility of each proposed means depends on which ontology of the human person one accepts as valid. Ethically, we must ask whether radical longevity or technologically-mediated immortality would be conducive to a human person's flourishing or well-being. This article summarizes the competing anthropologies that animate this discussion, and then critiques the Transhumanist ambition toward immortality, as contrasted by the Christian belief in eternal life. The article concludes with reasons supporting the value of increased longevity, but not radical life-extension aimed at temporal immortality using certain means favored by Transhumanists. Throughout the discussion, the philosophical and theological thought of Thomas Aquinas is taken as the foundational touchstone.